Effect of aqueous extract of leaves of Piper aduncum L. (PIPERACEAE) in the early development and cell cycle of Lactuca sativa L. (Lettuce) - de Assis Alves, Thammyres; Abeldt Christ, Jheniffer; Torres Leite, Cristiana; de Assis Alves, Thayllon; Miranda Praça-Fontes, Milene (Seven Editora, 2023)
Piperaceae is a family of basal angiosperms comprising about 3,615 species distributed in a pantropical form. In Brazil, there are about 458 species distributed in four genera, Piper L. and Peperomia Ruiz, and Pav. the most representative. Piper comprises shrubs and subshrubs. The best-known species of the genus is the black pepper (P. nigrum L.), a spice used for many years. Representatives of the genus are often used in folk medicine and the manufacture of medicines, as well as in the production of insecticides due to the properties of their essential oils. Among the most varied uses, oils can play an allelopathic or mutagenic role, and these are the objects of recent studies in several aromatic plants. Certain doses of these oils can inhibit or accelerate the growth of other vegetables. In addition, they can cause cellular changes that can lead to death. Based on this, this study aims to determine the concentrations of P. aduncum L. leaf extract that plays an allelopathic role and toxic gene cite in a model organism. The extract of P. aduncum was prepared from the leaves of 3 individuals, prepared at concentrations of 100 mg mL-1, 50 mg mL-1, 25 mg mL-1, and 12.5 mg mL-1. The design was completely randomized, with 5 treatments and 5 replications. Distilled water was used as a negative control. For allelopathy analysis, the following parameters were evaluated: germination speed index (GVI); germination percentage, root growth (CR), and aerial growth (AC). For the cytogenetic analysts, slides of the roots collected and fixed in ethyl alcohol: acetic acid by the crushing technique were prepared. The results show that the aqueous extract of P. aduncum leaves had an inhibitory effect on the germination and development of Lactuca sativa seeds, besides causing cellular changes such as bridges, C-metaphase, and chromosome loss. DOI: https://doi.org/10.56238/devopinterscie-180